Representasi Novel “Dua Garis Biru” karya Lucia Priandarini Dalam teori Feminisme - Nurrohman Salsabilla, Sinta; Lailiyatus Sa’diyah; Agus Hermawan; Saptono Hadi (Universitas Insan Budi Utomo, 2025)
Feminism is a social and political movement aimed at achieving gender equality between women and men. It challenges discrimination and injustices based on gender in society. Literature portrays aesthetic and linguistic beauty, a novel is a narrative prose literary work. The issue of feminism is currently highly popular among readers; through this article, it is hoped that the reality of feminism in the novel